Distribuição espacial e temporal dos casos de raiva animal diagnosticados entre 1996 e 2015 na região oeste do estado de São Paulo - Christofolli, Anavir Marcos (2020)
Rabies is an acute, fatal viral zoonosis caused by viruses of the genus Lyssavirus. The disease is sporadic in the West Paulista region, related to the presence of blood-sucking chiropterans and with intense livestock activity. The present study aimed to evaluate the spatial dispersion and temporal occurrence of cases of animal rabies diagnosed by the São Paulo Agribusiness Technology Agency (APTA), in municipalities located in the western region of the state of São Paulo, over a period of 20 years (1996 to 2015 ). For the execution of the analyzes, a database was created with 9,624 results of diagnoses for rabies in several animal species from 82 municipalities, of which 111 were positive. From the data, thematic distribution maps were performed and the Moran indices, local and general, were calculated. The temporal occurrence of the disease was assessed using the segmented regression method. It was found that in the five-year periods from 2001 to 2005 and 2006 to 2010, rabies was intensely registered in the municipality of Teodoro Sampaio, possibly associated with the wild fauna of Morro do Diabo State Park and in a nucleus composed by Álvares Machado, Narandiba, Pirapozinho, PresidenteBernardes, Presidente Prudente, RegenteFeijó, Taciba and Santo Expedito, whose night lights are highly attractive to insects, recognized as prey for non-hematophagous flies. It is concluded that rabies has decreased considerably in the region in recent years, however, the regional history suggests that areas of environmental preservation and populous zones offer risk for the occurrence of the infection.